PENERAPAN METODE VIKOR DALAM OPTIMASI PEMILIHAN JURUSAN DI UNIVERSITAS ROYAL - Raja Tama Andri Agus; Rina Julita; Mustika Fitri Larasati Sibuea; Gina Safira (Smart Education, 2025)
Abstract: Promotion is an activity carried out to convey, disseminate, and offer products, so that potential consumers are interested in buying. In the implementation of the promotion, CV. Pentaland Jaya abadi uses website media and brochures that still contain 2-dimensional images and information about housing so that potential consumers are less interested because consumers cannot see the exterior and interior shapes directly. Potential consumers usually get brochures through project locations that are still under construction, after that contact the marketing department. One way to solve this problem can be to use augmented reality technology with the appropriate development method is the Multimedia Development Life Cycle (MDLC) which includes Concept, Design, Material Collecting, Assembly, Testing, and Distribution so that this research can produce an android-based augmented reality application that can display 3 dimensional virtual shapes from 3 housing estates including calista haus, grand ayahanda residence and calista homey. From each housing produces 3 dimensional objects on the exterior and interior so that it can provide interest in buying house objects and in addition to that it also helps in the marketing department in promoting housing objects without the need to show many miniatures that require time and also large places.Â Keywords: Promotion, Brochure, Multimedia Development Life Cycle, AugmentedÂ Reality Abstrak: Pemilihan jurusan di universitas merupakan salah satu keputusan penting yang mempengaruhi karier dan masa depan seorang. Proses ini sering kali melibatkan berbagai pertimbangan, seperti minat pribadi, prospek karier, serta biaya pendidikan. Penelitian ini bertujuan untuk menerapkan metode VIKOR dalam membantu calon mahasiswa dalam memilih jurusan yang paling sesuai dengan preferensi mereka, berdasarkan kriteria-kriteria yang relevan. Metode VIKOR digunakan untuk mengatasi masalah pengambilan keputusan multi-kriteria, yang memungkinkan penentuan alternatif terbaik dengan mempertimbangkan berbagai faktor yang saling bertentangan. Dalam penelitian ini, tiga kriteria utama yang dipertimbangkan adalah minat pribadi, prospek karier, dan biaya pendidikan. Data diperoleh melalui survei yang melibatkan calon mahasiswa untuk mengidentifikasi preferensi mereka terhadap kriteria-kriteria tersebut. Hasil penelitian menunjukkan bahwa metode VIKOR dapat menghasilkan urutan prioritas jurusan yang optimal, di mana jurusan yang paling sesuai dengan preferensi seseorang dapat dipilih secara objektif dan terstruktur. Penelitian ini memberikan wawasan baru dalam penggunaan teknik pengambilan keputusan multi-kriteria untuk membantu calon mahasiswa dalam menghadapi proses pemilihan jurusan yang kompleks dan penuh pertimbangan.Â Kata kunci: Promosi, Brosur, Multimedia Development Life Cycle, Augmented Reality